Makaanatu Ilmi Al-Lughah At-Tathbiiqiy Fii Ta’liimi Al-Lughah Al-Arabiyyah Li An-Naathiqiina Bi Ghoiriha - Sodik, Achmad Ja'far; Muhammad Aminuddin; Uril Bahruddin (Uktub: Journal of Arabic Studies, 2023)
This research aims to; know the concrete form of applied linguistics and learning Arabic; understand the emergence of applied linguistics and its sources in learning Arabic; describes the position of applied linguistics in learning Arabic for non-Arabs. The method in this study uses an approach that uses reference literature with initial information used from books, magazines and related sources. The data collection used is the documentation method by presenting the data and concluding it. The research results show that; Applied linguistics is part of linguistics or linguistics which discusses the application of various scientific studies in the field of linguistics and learning Arabic is a learning process that involves teachers and students in achieving world learning goals, namely Arabic; The emergence of applied linguistics emerged as a field of science around 1946 and sources of applied linguistics are divided into linguistics, psychology, sociology, and pedagogy; position of applied linguistics in language learning for non-Arabic speakers, which includes 3 main principles, namely educational principles, psychological principles and linguistic principles.